Análisis de re-importación en el sector bananero, determinación de culpas y definir medidas correctivas para la asociación “El Guabo”. - San Martin Cruz, Evelyn Tatiana (My University, 2019)
The objective of this study is to determine what were the causes or reasons for banana contamination during export. In order to apply corrective measures in the post production or verification of the pallets avoiding unnecessary and irreparable losses, because the fruit is a perishable product and at the time of being contaminated, the indicated personnel makes the decision to eliminate the merchandise to avoid the spread of pests and deny the option of reimportation to the country of origin. It should be noted that the Association of Small Banana Producers ¨El Guabo¨ (APPBG) should be more precise and plentiful to implement strategies and continue to be maintained in national and international marketing, emphasizing that in European countries they are demanding in the issue of quality. On the other hand, the company should continue with its productive activity since for several years it has provided jobs and has generated the income of foreign currency for the economy of Ecuador. We have to be clear that the competences of companies today is hard, obtaining as a result the options of producing organic bananas, avoiding the use of materials such as fertilizers, pesticides or any other chemical element that contaminates the environment. Organic fruits are attracting a lot of attention in the international market because they promote the preservation of natural resources worldwide.
El objetivo de este estudio es determinar cuáles fueron las causas o motivos para que el banano se contamine durante la exportación. Con el fin de aplicar medidas correctivas en la post producción o verificación de los pallets evitando perdidas innecesarias e irreparables, debido que la fruta es un producto perecible y al momento de estar contaminada, el personal indicado toma la decisión de eliminar la mercancía para evitar la propagación de plagas y negar la opción de reimportación al país de origen. Cabe destacar que la empresa Aso-Guabo deberá ser más precisa y caudalosa para implementar estrategias y poder seguir manteniéndose en la comercialización nacional e internacional, acentuando que en los países europeos son exigentes en el tema de calidad. Por otro lado la empresa debería seguir con su actividad productiva ya que durante varios años ha brindado plazas de trabajo y ha generado el ingreso de divisas para la economía de Ecuador. Tenemos que tener en claro que las competencias de las empresas en la actualidad es dura, obteniendo como resultado las opciones de producir banano orgánico evitando utilizar los materiales como: fertilizantes, pesticidas o cualquier otro elemento químico que contamine el medio ambiente. Las frutas orgánicas están llamando mucho la atención en el mercado internacional por que fomenta a nivel mundial la preservación de los recursos naturales.
Keywords: RÉGIMEN ADUANERO; GO ORGÁNICO DE LA PRODUCCIÓN COMERCIO E INVERSIONES (COPCI); COMERCIO INTERNACIONAL; ADUANA; RECHAZO DE BANANO